Early psychosocial intervention does not delay institutionalization in persons with mild Alzheimer disease and has impact on neither disease progression nor caregivers' well‐being: ALSOVA 3‐year follow‐up. (14th July 2015) - Koivisto, Anne M.; Hallikainen, Ilona; Välimäki, Tarja; Hongisto, Kristiina; Hiltunen, Asta; Karppi, Pertti; Sivenius, Juhani; Soininen, Hilkka; Martikainen, Janne
Abstract : Objectives: Early diagnosis, initiation of Alzheimer's disease (AD) therapy and programs that support care of persons with AD at home are recommended. The objective of this study was to assess the effect of early psychosocial intervention on delaying the institutionalization of persons with AD. We also assessed the influence of intervention on AD progression, behavioral symptoms, and health‐related quality of life (HRQoL) in persons with AD and caregivers. Methods: Kuopio ALSOVA study, a prospective, randomized intervention study with a 3‐year follow‐up, was carried out at memory clinics. Home‐dwelling persons with very mild or mild AD ( n = 236) and AD‐targeted therapy and their family caregivers ( n = 236) were randomized to the intervention or control group (1:2). Psychosocial intervention including education, counseling, and social support was given during the first 2 years (16 days). The primary outcome was the cumulative risk (controlled for death) of institutionalization over 36 months. Secondary outcomes were adjusted mean changes from baseline in disease severity, cognition, daily activities, behavior, and HRQoL for persons with AD; and change in psychological distress, depression, and HRQoL for caregivers. Results: No differences were found in nursing home placement after the 36‐month follow‐up between intervention and control groups. No beneficial effects of the intervention were found on the secondary outcomes. Conclusions: The psychosocial intervention did not delay nursing home placement in persons with AD and had no effect on patient well‐being, disease progression, or AD‐related symptoms or caregiver well‐being. Instead of automatically providing psychosocial intervention courses, individualized support programs may be more effective. Copyright © 2015 John Wiley & Sons, Ltd.